2010
DOI: 10.1118/1.3431575
|View full text |Cite
|
Sign up to set email alerts
|

Influence of beam efficiency through the patient‐specific collimator on secondary neutron dose equivalent in double scattering and uniform scanning modes of proton therapy

Abstract: The results of these experiments suggest that the patient-specific collimator is a significant contributor to the secondary neutron dose equivalent to a distant organ at risk. Improving conformity of the radiation field to the patient-specific collimator can significantly reduce secondary neutron dose equivalent to the patient. Therefore, it is important to increase the number of available generic field sizes in double scattering systems as well as in uniform scanning nozzles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…This is because the collimators are located close to the patient, and many primary particles stop at this location in the beam line (Brenner et al, 2009;Yonai et al, 2009;Hecksel et al, 2010).…”
Section: Out-of-field Volumementioning
confidence: 99%
See 1 more Smart Citation
“…This is because the collimators are located close to the patient, and many primary particles stop at this location in the beam line (Brenner et al, 2009;Yonai et al, 2009;Hecksel et al, 2010).…”
Section: Out-of-field Volumementioning
confidence: 99%
“…(ii) Beam parameters (105) The influences of beam parameters have been investigated by several groups (Polf and Newhauser, 2005;Mesoloras et al, 2006;Zheng et al, 2007;Yonai et al, 2008;Athar and Paganetti, 2009;Shin et al, 2009;Hecksel et al, 2010). The following parameters are considered to have the main effects on the neutron dose to patients in ion beam radiotherapy using the broad beam method.…”
Section: Out-of-field Volumementioning
confidence: 99%
“…The efficiency of most proton therapy treatment heads is quite low (typically only between 3 and 30% depending on the field size). The neutron dose depends on the ratio of field size to aperture opening and neutron doses from treatment head neutrons typically increase with decreasing field size (Mesoloras et al 2006; Zacharatou Jarlskog et al 2008; Hecksel et al 2010). It has been shown that for a small target volume, the contribution of neutrons from the treatment head can reach ~99 % of the total neutron contribution, while for a large target volume it can go down to ~60 % (Zacharatou Jarlskog et al 2008).…”
Section: Studies To Estimate the Risk For Second Cancersmentioning
confidence: 99%
“…1,[9][10][11][12][13][14] There are a few reports of neutron doseequivalent measurements made in proton therapy centers with either the wide-energy neutron detection instrument (WENDI) or smart WENDI (SWENDI), a type of Rem-meter that is sensitive over an energy range adequate for measuring neutrons from proton therapy. [14][15][16][17] Like standard Remmeters, however, these detectors provide only a single doseequivalent value and do not provide the neutron spectrum. There are also several reports of measurements with detectors such as track etch detectors 14,18 or thermoluminescent detectors 19 that have limited or no response to neutrons with energies greater than 10 MeV.…”
Section: Introductionmentioning
confidence: 99%